THE ROLE OF NURSES IN SURGICAL OPERATIONS (Modern education and development, 2024)
This article highlights the essential responsibilities of nurses during surgical operations, focusing on their critical role in ensuring patient safety, assisting the surgical team, and providing comprehensive care before, during, and after surgery. Nurses in surgical settings, particularly those working as scrub nurses, circulating nurses, and recovery room nurses, are involved in various tasks ranging from preparation, assisting in surgery, and managing postoperative care. Their expertise, collaboration with the surgical team, and application of evidence-based practices ensure successful surgical outcomes and optimal patient recovery.